Melt‐Processing of Complementary Semiconducting Polymer Blends for High Performance Organic Transistors. Issue 6 (5th December 2016) - Zhao, Yan; Zhao, Xikang; Roders, Michael; Gumyusenge, Aristide; Ayzner, Alexander L.; Mei, Jianguo
Abstract : Melt‐processing of complementary semiconducting polymer blends provides an average charge carrier mobility of 0.4 cm 2 V −1 s −1 and current on/off ratios higher than 10 5, a record performance for melt‐processed organic field‐effect transistors.